MOBILE APPLICATION AS A TOOL FOR FORMING DIGITAL AND METHODOLOGICAL COMPETENCE OF FUTURE TEACHERS OF NATURAL DISCIPLINES - Банак, Роман (Modern engineering and innovative technologies, 2025)
The article is devoted to the study of the possibilities of the mobile application "Virtual Cabinet" as an innovative means of forming research, digital and methodological competencies in the process of teaching natural disciplines in institutions of gene